STUDY OF LEGAL DISCIPLINES BY INTERACTIVE DISTANCE LEARNING - Kryshtanovych, Myroslav (Mountain School of Ukrainian Carpaty, 2020)
The article examines the current practice of teaching legal disciplines for future lawyers, which has a rich arsenal of various and effective methods, techniques and training tools, including interactive ones, which fully help to reveal the full specifics of a particular legal discipline. Interactive whiteboards, electronic textbooks, and tutorials that include text, graphics, photos, and video snippets are widely used in exploring and explaining individual topics. The use of such tools significantly intensifies the educational process. It should be noted that interactive technologies provide simple and convenient tools for solving a wide range of tasks in the field of education of future lawyers. They help to create learning conditions so that students enjoy learning, seek to improve their learning outcomes, and are aware that they will continue to apply their knowledge successfully in practice. The most effective means of studying the legal disciplines by means of interactive distance learning during higher education institutions have been established. First of all, it concerns the use of the interactive whiteboard in the educational process. The use of the interactive whiteboard, as a traditional element of the educational process, is widely used in lectures, seminars, presentations. The interactive whiteboard is a flexible tool that combines the simplicity of a regular marker board with the capabilities of a computer. It provides the necessary training page from the Internet, demonstrates the necessary information. It should be noted that anything that is drawn or written on the interactive whiteboard during the lesson can be saved as computer files, printed, and emailed. Therefore, the role and importance of the interactive practice of teaching legal disciplines allows us to determine the most effective interactive teaching of professional disciplines for future lawyers. Thus, its use significantly intensifies the work of future lawyers in the classroom.